1980
DOI: 10.1007/bf00845053
|View full text |Cite
|
Sign up to set email alerts
|

The effects of psychological factors and physical trauma on recovery from oral surgery

Abstract: This study evaluated the effects of several psychological factors on postsurgical recovery while controlling for and also evaluating the effects of the physical trauma induced by the surgery. Subjects were 38 patients (18 males and 20 females) who were scheduled to have four third molars surgically removed. The psychological factors measured included anxiety and expectations about recovery, trait anxiety, coping behaviors, and health locus of control. Surgical trauma was rated after surgery, and the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 21 publications
3
60
1
Order By: Relevance
“…Hansson et al (1989) did not find an association between presurgical stress or tension and pain after third molar surgery but found a high correlation between pain and analgesic intake. George et al (1980) found that expectancies and anxiety significantly predicted medication intake, but to a lesser extent patients' pain. Analgesic intake may obscure the relations between psychological predictors and pain since anxious patients may take more pain medication and then experience less pain.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Hansson et al (1989) did not find an association between presurgical stress or tension and pain after third molar surgery but found a high correlation between pain and analgesic intake. George et al (1980) found that expectancies and anxiety significantly predicted medication intake, but to a lesser extent patients' pain. Analgesic intake may obscure the relations between psychological predictors and pain since anxious patients may take more pain medication and then experience less pain.…”
Section: Discussionmentioning
confidence: 97%
“…Next, adolescents' trait-NA and expectancies about recovery were entered as affective and motivational parameters, respectively. Expectancies and NA were entered before other psychosocial measures since they were seen as having a primary impact on outcome (George et al, 1980;Scheier et al, 1989). In the third stage, anticipated parental pampering responses were entered as reflecting learned family patterns which may affect disability and pain (Walker and Zeman, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodological and measurement heterogeneity across the studies may have also contributed to variance in effect sizes in the meta-analysis. Interestingly, clinical and tape-stripping studies were the only wound types to report nonsignificant findings [61,66] in the meta-analysis. In addition, it is worth noting that none of the tape stripping studies formally discussed the validity and reliability of their transepidermal water loss measurements, although one study [48] did state that procedural guidelines were followed.…”
Section: Discussionmentioning
confidence: 99%
“…His causality model, which refers solely to reduced oxygen supply, can today be considered outdated. In the early 1980s, George et al [1980] published a study in which psychological personality characteristics were studied with respect to convalescence following surgical procedures. They postulated that certain psychological personality characteristics lead to more complications and poorer wound healing.…”
Section: Studies On Emotions and Wound Healingmentioning
confidence: 99%